Psychological Predictors of Resilience in Parents of Insulin-Dependent Children and Adolescents - Mitra Edraki; Masoume Rambod (International Journal of Community Based Nursing and Midwifery, 2018)
Background: Parents of insulin-dependent children and adolescents need resilience to continue their lives. The aim of this study was to determine the psychological predictors of resilience in parents of insulin-dependent children and adolescents. Methods: This was a descriptive correlational study performed in 2016. One hundred and thirteen parents of children and adolescents with diabetes who referred to a diabetes clinic in Shiraz participated in this study. Convenience sampling was used. Depression Anxiety Stress Scales (DASS-21) and Connor-Davidson Resilience Scale (CD-RISC) (25 items) were also used. The data were analyzed by SPSS software version 20 using t-test, ANOVA, Pearson correlation coefficients, and linear regression analysis. P<0.05 was considered as significant. Results: The findings showed that the mean±SD score of resilience was 65.33±23.81 in parents of children and adolescents with diabetes. Indeed, 45.1% of the parents had mild to extremely severe levels of stress. Besides, 58.4% and 71.4% of them reported mild to extremely severe depression and anxiety, respectively. The lowest mean±SD scores of resilience were reported in parents with extremely severe levels of depression (37.57±16.26), anxiety (44.89±23.53), and stress (37.84±17.90). Moreover, 49% of changes in resilience was explained by such factors as stress, anxiety, depression, and life and health satisfaction. Among these variables, the association between resilience and depression (t=-6.97, P<0.001) and life satisfaction (t=-3.18, P=0.002) were statistically significant. Conclusion: Since nearly half of the parents experienced stress, depression, and anxiety, and there was an association between resilience and these psychological variables, parents’ psychological problems, especially depression, might be reduced by improving their resilience.